ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SETELAH PANDEMI COVID-19: STUDI KASUS PERUSAHAAN LOGISTIK PADA TOP 50 ALPHALINER - Aryani, Rahma Listy; Alam, Muhammad Dimar (E-Jurnal Akuntansi TSM, 2025)
This study aims to provide empirical evidence regarding differences in financial performance, represented by current ratio (CR), return on assets (ROA), debt to equity ratio (DER), and operating expenses ratio (OER), in logistics companies before and after the COVID-19 pandemic. This comparative research applied the Wilcoxon Signed Rank test, with purposive sampling selecting 18 logistics companies listed in the Top 50 Alphaliner as of December 14, 2024, as the research sample. The results show significant differences in CR and ROA, with both being higher after the pandemic, while OER shows lower values after the pandemic. Meanwhile, DER does not exhibit significant differences between the periods before and after the pandemic. These findings indicate that CR, ROA, and OER are more sensitive to external changes compared to DER, which tends to remain stable.